To solve the problem, let's go through the steps for both Part A and Part B.
Part A
We start with the equation: \[ 12x^2 - 18x = 0 \]
To factor out the Greatest Common Factor (GCF), we first identify the GCF of the coefficients 12 and 18, which is 6.
Now we can factor out \(6x\): \[ 6x(2x - 3) = 0 \]
So the correct response for Part A is: 6x(2x−3)=0
Part B
Now, we need to find the solutions by setting the factored expression equal to zero: \[ 6x(2x - 3) = 0 \]
This gives us two factors:
- \( 6x = 0 \)
- \( 2x - 3 = 0 \)
Solving these:
-
From \( 6x = 0 \): \[ x = 0 \]
-
From \( 2x - 3 = 0 \): \[ 2x = 3 \] \[ x = \frac{3}{2} \]
Thus, the two solutions are: \[ x = 0 \quad \text{and} \quad x = \frac{3}{2} \]
So the correct response for Part B is: x=0 and x=32 (where \(32\) represents \( \frac{3}{2} \)).
Therefore, the two parts are correctly answered as:
- Part A: \(6x(2x−3)=0\)
- Part B: \(x=0 \text{ and } x=\frac{3}{2}\) (interpreted as \(x=32\)).